"Supreme among our Valuables": Whale Teeth Tabua, Chieftainship and Power in Eastern Fiji - Hooper, Steven (Waka Kuaka, 2013)
This article draws on recent ethnographic research and on records and observations from the early 19th century onwards to demonstrate the great importance of transactable tabua "modified whale teeth" in Fijian cultural life. It argues for a distinction between these post-contact transactable tabua and heirloom tabua of greater antiquity, but suggests that the role of the latter as embodiments of pre-Christian gods partly accounts for the high value still accorded to transactable tabua and their close association with chiefs.